2015
DOI: 10.1242/jeb.130559
|View full text |Cite
|
Sign up to set email alerts
|

On doing two things at once: dolphin brain and nose coordinate sonar clicks, buzzes, and emotional squeals with social sounds during fish capture

Abstract: Dolphins fishing alone in open waters may whistle without interrupting their sonar clicks as they find and eat or reject fish. Our study is the first to match sound and video from the dolphin with sound and video from near the fish. During search and capture of fish, free-swimming dolphins carried cameras to record video and sound. A hydrophone in the far field near the fish also recorded sound. From these two perspectives, we studied the time course of dolphin sound production during fish capture. Our observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
64
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 49 publications
6
64
1
Order By: Relevance
“…Click train characteristics have been associated with foraging/feeding in bottlenose dolphin (Au 1993, Nowacek 2006, Jensen et al 2009, Ridgway et al 2015. Compared to Melcon et al (2012) who found abundant click production during feeding behavior, few click sounds were registered in this study.…”
mentioning
confidence: 53%
“…Click train characteristics have been associated with foraging/feeding in bottlenose dolphin (Au 1993, Nowacek 2006, Jensen et al 2009, Ridgway et al 2015. Compared to Melcon et al (2012) who found abundant click production during feeding behavior, few click sounds were registered in this study.…”
mentioning
confidence: 53%
“…They are composed of two identical sound producing structures consisting of fatty dorsal bursae within a pair of phonic lips, one in the left and one in the right nasal passage (Cranford et al, 1996). A recent study suggested that the two dolphin brain hemispheres, which sleep independently (Lyamin et al, 2008), may also act independently when it comes to coordinating prey capture and communication with simultaneously emitted echolocation clicks and social sounds (Ridgway et al, 2015).…”
Section: Behavioral Data On Auditionmentioning
confidence: 99%
“…Experimental studies have demonstrated singularities on the sound emission of dolphins in which both echolocation and communication sounds are emitted simultaneously (Ridgway et al, ) and with specific source locations: the echolocation signals were produced in the right side of the epicranial complex, while the left side was used for communication sounds, such as whistles and pulsed calls (Madsen et al, ). Although, it has been demonstrated that the biosonar beam originates more or less at the center in T. truncatus (Moore et al, ; Finneran et al, ), the source center of the right sound beam may be adjusted by means of the mobility of the nasal plugs by retraction of the nasal plug muscles during vocalizing (Mead, ; Heyning and Mead, ).…”
mentioning
confidence: 99%